Biosafety materials for tuberculosis treatment - Wei Wang; Hui Guo; Siqi Lin; Xue Xiao; Yaling Liu; Yupeng Wang; Dongfang Zhou (Biosafety and Health, 2022)
Tuberculosis (TB) is among the deadliest infectious diseases worldwide. Although the existing antituberculosis (anti-TB) drugs remain to be effective, the administration of these complex anti-TB drug combinations with obvious toxicity often leads to patients’ nonadherence. This may contribute toward the emergence of drug-resistant strains as well as lead to treatment failure and relapse. Therefore, in the past half century, the main focus of anti-TB drug research was to reduce the frequency of administration and toxicity and improve patients’ compliance and drug sensitivity. Following these principles, the development of engineered biosafety materials is one of the most effective and promising methods in resolving these challenges. Compared with traditional drugs, biosafety materials provide a viable platform for treating TB, which are beneficial in reducing the frequency of drug administration and systemic toxicity, improving patients’ compliance and drug sensitivity, and enhancing drug targeting. In this review, we summarized the application of biosafety materials in treatment of TB in recent years and discussed the challenges faced when developing a safe, more effective, and economical pharmacotherapy against TB.